Functional approaches in translation studies in Germany - Paul Kussmaul (Ilha do Desterro)
In the early phase of translation studies in Germany, contrastive linguistics played a major role. I shall briefly describe this approach so that the functional approach will become clearer by contrast. Influenced by the representatives of stylistique comparée, Vinay/Darbelnet (1968) Wolfram Wilss, for instance, in his early work (1971, 1977) makes frequent use of the notion transposition (German “Ausdrucksverschiebung“, cf. also Catford’s (1965) term shift). As a whole, of course, Wilss’ work has a much broader scope. More recently, he has investigated the role of cognition (1988) and the various factors in translator behaviour (1996). Nevertheless, transposition is still a very important and useful notion in describing the translation process. The need for transpositions arises when there is no possibility of formal one-to-one correspondence between source and target-language structures. The basic idea is that whenever there is a need for transposition, we are faced with a translation problem.